Initial development of tree species in agroforestry systems in the Lower Amazon, Pará, Brazil - Rayol, Breno Pinto; Alvino-Rayol, Fabrízia de Oliveira (Revista de Ciências Agroveterinárias, 2019)
Studies on the initial development of tree species in agroforestry systems are important, since they provide subsidies for the management of these agroecosystems. The objective of this research was to evaluate the survival and height growth of tree species changes in Amazonian agroforestry systems subjected to different forms of area preparation and management. The experiment was carried out in two agroforestry systems (successional and agroforestry consortium) located in Lower Amazon, western Pará state. In the commercial agroforestry consortium, the survival rate of the species didn’t exceed 70%. In the successional system, the survival rate of the implanted tree species was high, with most values varying between 90 and 100%. Water stress in the driest periods of the year is a limiting factor in the adoption of agroforestry systems in the region, causing mortality of the seedlings. Regarding the growth in height, the evaluated species obtained satisfactory performances in both systems.